AMALAKI AS PREVENTING PREMATURE AGEING DRUG-A REVIEW - Rajan, Sujata; Kumari, Shikha (International Journal of Ayurveda and Pharma Research, 2016)
Ageing is the natural process of decaying continuously and this manifest in the form of various degenerative changes. Ayurveda has two aims i.e. prevention and maintenance of health from diseases and cure from disease. Everyone wants to give the impressing of being young forever and increase life span by staying healthy. As various cells and tissues of the body undergo changes as age advances Rasayana claims that it retards the process of ageing. The word Rasayana connotes a specific meaning Rasyana means by which body get excellence of Rasa which nourishes the body. It basically boosts the Oja and the immune system. It helps the person to maintain good health and longevity. Rasayana drugs acts as antioxidants and neuroendocrine immunomodulators and Amalaki is one of them. Oxidative damage to cells is important phenomenon in ageing process. Charak and Vaghbat has admired Amalaki as the drug of choice for Vayasthapana karma (to stop ageing). Charak has also mentioned it as Ayushya, Deepaniya (appetizer) and Pachniya (digestive). Amalaki is the great Rasayana that helps to protect from disease and reduced the possibilities of pre mature ageing. It acts on Rakta Dhatu Main constituents of Amalaki are Vit. C, carotene and riboflavin. It is having a role in cellular oxidation reduction. They also play a role in collagen fibrin formation, helps in production of fibrin, and iron absorption.